Cultural Heritage, Sustainable Development, and Climate Policy: Comparing the UNESCO World Heritage Cities of Potsdam and Bern - Kristine Kern; Janne Irmisch; Colette Odermatt; Wolfgang Haupt; Ingrid Kissling-Näf (Sustainability, 2021)
Developing sustainable, carbon-neutral, and climate-resilient districts seems to be particularly challenging with respect to historic city centers. However, barriers posed by legal requirements for historical buildings are counterbalanced by opportunities because historic cities have not undergone urban modernization and did not embrace the concept of functional cities, which nowadays impedes urban sustainability transformations. Thus, this paper focuses on the relationship between cultural heritage, urban sustainable development, and climate policy. We study continuity and change in the mid-sized UNESCO World Heritage cities Potsdam (Germany) and Bern (Switzerland). These matching forerunner cities share many characteristics, which enables them to transfer policies and jointly create new solutions for common problems. We find that national context matters, but we also identify functional equivalents like referenda and active citizen participation. Despite many similarities, Potsdam is ahead of Bern with respect to the institutionalization and integration of climate mitigation and adaptation. The comparative analysis (interviews and document analysis) identifies innovations that can be transferred between the two cities (e.g., Potsdam's integrative climate policy or Bern's efforts to become a role model for stakeholders and citizens). Moreover, the challenge to coordinate heritage management and climate governance offers chances for cooperation between matching cities like Bern and Potsdam.
Keywords: 320; climate policy; sustainable development; governance; UNESCO World Heritage; (urban) heritage management; historical cities; forerunner cities; matching cities; city of Potsdam; city of Bern